Developing mobile commerce PCOnlineShop using Rapid Application Development (RAD) / Maserairani Ab Rahman - Ab Rahman, Maserairani (2014)
This research study is about developing mobile commerce for KISTECH Sdn.Bhd. Researcher found that this company does not have any online system in selling their IT Products. Method that currently been used by this company to sell their products only through advertisement in website, media social such as Facebook and pamphlets. The goal of this research is mainly focused on the development of mobile commerce PCOnlineShop using Rapid Application Development (RAD) for KISTECH Sdn.Bhd. It was intended to study the development of Mobile commerce online system development using RAD methodology which help researcher in better understanding about RAD methodology which it consists of five main phases which is problem identification and planning, requirements gathering, design analysis, prototype development and user review. This thesis research has two objectives that need to be achieved. The first objective is to investigate the requirements and the elements of Mobile commerce PCOnlineShop interfaces for KISTECH Sdn Bhd. The second objective is to develop mobile commerce PCOnlineShop for KISTECH Sdn.Bhd using Rapid Application Development (RAD). This project will interview user using qualitative research method related to the understanding of some aspect of social life. According to the studies, it is a wise solution for merchandise to be sold using online system. At the same times, it focuses on mobile commerce element instead of full website version when browsing the system using smartphones. By providing mobile commerce PCOnlineShop, users can sell IT Products using this online system. As a result, this project help to increase the quality of mobile commerce design features elements, customer satisfaction, improve their method of selling products using mobile commerce online system and will increase company revenues. However, the researcher found that PCOnlineShop still need future system amelioration such as providing the online payment and a new function can be added in future such as abandon shopping cart functions to remind the users and new design for this mobile commerce that will be more effective and interactive system.